Working Together to Implement Gender-Responsive Policing: Gender Advisory Work in Timor-Leste - Loene M Howes; Suzanne Preston (International Journal for Crime, Justice and Social Democracy, 2025)
For sustainable development to occur in post-conflict contexts, security concerns need to be addressed. Gender-responsive policing aims to provide policing for all community members. The Timor-Leste Police Development Program (TLPDP) is a bilateral partnership between Timor-Leste and Australia, supporting the Polícia Nacional de Timor-Leste (PNTL) to develop capacity in areas of identified need. This includes reducing sexual and gender-based violence. Delivered by the Australian Federal Police, the program is informed by a gender strategy that reflects international agreements on gender, security, and human rights. This article draws on program design, evaluations, reports, and experience, to explore how strategic objectives on gender have been translated into practical initiatives of the TLPDP. Initiatives include a gender audit of the PNTL, a scoping review of the vulnerable persons units, specialist training courses, and community awareness campaigns. The article highlights the role of strategic alignment, partnership, and collaboration within and beyond policing to amplify efforts.